METHODOLOGICAL PROFILES OF THE CIVIL SOCIETY: CIVIC VIRTUE VERSUS CIVIL ASSOCIATION - Marius Povilas Povilas Šaulauskas (Problemos, 1999)
The article approaches a complex methodological and conceptual plexus backing the heavily employed concept of Civil Society in the numerous contexts of professional and popular discourses. An author argues for the central distinction between precise, technical (sensu stricto) and rough, popular (grosso modo) usage the term. The professional sensu stricto usage of the concept unfolds and could be as such identified only on the diachronic and synchronous background of different theoretical contexts that were articulated in the millennial history of ever controversial Western philosophical discourse. The horizon of its possible meaning is extremely differentiated and connot be summarized in an all-embracing universaly valid meaning. The laic grosso modo usage of the notion, in contrast, is included in a variety of political, cultural and other column-type popular vocabularies. Here the cluster of meanings attached to the notion Civil Society accords to the synchronous patterns of contextualization and, although altogether deprived of deliberate methodological backing and conceptual clarity, it could be roughly identified in terms of loosely defined finite list of connotations at any given momentum of time. An heuristically sound approximating definition of the Civil Society sensu stricto that is nevertheless required in a consistent empirically backed societal analysis cannot claim universal validity and must be posited only instrumentally. An example of such an instrumental concept of Civil Society which by itself falls within the class of sensu stricto connotations of the term is also offered.